The Ancient Theravāda Meditation System, Borān Kammaṭṭhāna: Ānāpānasati or 'Mindfulness of The Breath' in Kammatthan Majjima Baeb Lamdub. (18th January 2016) - Skilton, Andrew; Choompolpaisal, Phibul
Abstract : In Thailand the pre-reform Theravāda meditation system, borān kammaṭṭhāna, is now practised only by small and isolated groups. To promote detailed comparative study of borān kammaṭṭhāna, the tradition of it taught at Wat Ratchasittharam, Thonburi, is explored through a translation of a text on ānāpānasati attributed to Suk Kaitheun, the head of its lineage. This is followed by a detailed discussion and comparison with the description of the same technique in the Visuddhimagga. Some close connections between these two sources are identified and it is speculated that, despite features concerning nimitta, bodily location, terminology etc. that are diagnostically distinctive for borān kammaṭṭhāna, its method for ānāpānasati can be seen as a rational development of earlier techniques advocated by Buddhaghosa.